Reactivation of mutant p53 in esophageal squamous cell carcinoma by isothiocyanate inhibits tumor growth - Guan, Lulu; Yang, Yalan; Lu, Yao; Chen, Yu; Luo, Xi; Xin, Dao; Meng, Xiangrui; Shan, Zhengzheng; Jiang, Guozhong; Wang, Feng (Frontiers in Pharmacology, 2023)
p53 mutations are prevalent in human cancers; approximately half of patients with esophageal cancer present these mutations. Mutant p53 (mutp53) exerts oncogenic functions that promote malignant tumor progression, invasion, metastasis, and drug resistance, resulting in poor prognosis. Some small molecules have been shown to mitigate the oncogenic function of mutp53 by restoring its wild-type activity. Although these molecules have been evaluated in clinical trials, none have been successfully used in the clinic. Here, we investigated the antitumor effects of phenethyl isothiocyanate (PEITC) in p53-mutant esophageal squamous cell carcinoma (ESCC) and elucidated its mechanism to identify new therapeutic strategies. We observed that p53R248Q is a DNA contact mutation and a structural mutation and that PEITC can restore the activity of p53R248Q in vitro and in vivo, further clarifying the antitumor activity of PEITC in cancers with different types of p53 mutations. PEITC can inhibit ESCC growth, induce apoptosis, and arrest cell cycle progression and has a preferential selectivity for ESCC with p53 mutations. Mechanistic studies showed that PEITC induced apoptosis and arrested cells at G2/M transition in cells expressing the p53R248Q mutant by restoring the wild-type conformation and transactivation function of p53; these effects were concentration dependent. Furthermore, PEITC inhibited the growth of subcutaneous xenografts in vivo and restored p53 mutant activity in xenografts. According to these findings, PEITC has antitumor effects, with its ability to restore p53R248Q activity being a key molecular event responsible for these effects.